2022
DOI: 10.3389/fpsyg.2021.762000
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Input in the Grammatical Expression of Stance: A Collexeme Analysis of the INTRODUCTORY IT PATTERN

Abstract: Previous research on the INTRODUCTORY IT PATTERN unveiled various lexical and grammatical aspects of its use as a grammatical stance device, including the range of the most frequently used adjectival and verbal stance lexemes, associated stance meanings, the most frequent sub-patterns, and the distinct uses in various contextual settings of the pattern. However, the stance meanings of the pattern, which are deeply rooted in the associated lexical resources, are still understudied. This study explores the meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Furthermore, although the Stance Triangle is modality agnostic in theory, traditionally, the focus of stance-taking research has been on lexico-grammatical and to a lesser extent prosodic means ( Biber and Finegan, 1989 ; Couper-Kuhlen, 2012 ; Wang et al, 2022 ). Over the past years, interest in multimodal research on stance-taking has increased ( Andries et al, 2023 ).…”
Section: Theoretical Background and Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although the Stance Triangle is modality agnostic in theory, traditionally, the focus of stance-taking research has been on lexico-grammatical and to a lesser extent prosodic means ( Biber and Finegan, 1989 ; Couper-Kuhlen, 2012 ; Wang et al, 2022 ). Over the past years, interest in multimodal research on stance-taking has increased ( Andries et al, 2023 ).…”
Section: Theoretical Background and Rationalementioning
confidence: 99%
“…While the Stance Triangle can be considered as a 'snapshot' of the stance at a given moment in interaction, Iwasaki (2022, p. 15) highlights that "all aspects of the stance activity are in constant motion and emerge across several turns along the temporal trajectory during an interaction". Furthermore, although the Stance Triangle is modality agnostic in theory, traditionally, the focus of stance-taking research has been on lexico-grammatical and to a lesser extent prosodic means (Biber and Finegan, 1989;Couper-Kuhlen, 2012;Wang et al, 2022). Over the past years, interest in multimodal research on stance-taking has increased (Andries et al, 2023).…”
Section: Multimodal Stance-takingmentioning
confidence: 99%
“…It was found that the evaluative it pattern is typical and representative, and this style is characterized by its frequency of use, evaluation adjectives, and evaluation clause pattern in different registers. Wang Z. et al (2022) explored the significance of the evaluative it pattern with reference to the stance meaning of patterns associated with adjective and verb lexemes. The findings showed that the co-occurrence morphemes of adjectives and verbs were statistically and functionally significant for each stance type/subtype provided.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Whereas the large majority of studies have focused on lexico-grammatical means (see e.g. Biber and Finegan, 1989;Du Bois, 2007;Wang et al, 2022) and to a lesser extent prosodic resources (Couper-Kuhlen, 2012) for expressing stance, the stance-taking potential of other embodied resources has only recently attracted systematic attention. This can be explained, at least in part, by a more general multimodal turn in Conversation Analysis (Goodwin, 2000;Deppermann, 2013;Mondada, 2019), usage-based linguistics (Feyaerts et al, 2017;Perniss, 2018) and other fields.…”
Section: Introductionmentioning
confidence: 99%